Methods of privatization and economic growth in transition economies - John Bennett; Saul Estrin; Giovanni Urga (Transformation, Integration and Globalization Economic Research (TIGER), 2006)
Dynamic panel data methods are used to estimate a growth model using data from 23 transition countries for the period 1990 to 2003. The estimating equation is augmented with country- and time-specific variables for methods of privatization and other factors potentially relevant to growth in transition economies. It is found that 'mass privatization' is associated with faster growth, but the other privatization methods have no significant impact. The findings suggest that in the countries that used mass privatization the long-term growth process may have been accelerated by the evolution of ownership structure and the speed with which the links between the state and firms were severed.
Keywords: L33; O40; P27; P31; C23; C33; 330; privatization; transition economies; economic growth; panel data; Privatisierung; Wirtschaftswachstum; Wachstumstheorie; Schätzung; Transformationsstaaten